Pinus spp. IN THE PRODUCTION OF ORIENTED STRAND BOARD (OSB) - Mendes, Lourival Marin (2005)
This work had the objective to study the species effects, and the wax addition in the OSB panels properties. The final conclusion was that the studied species are homogeneous among themselves and they produce similar quality panels. The produced panels attended to the minimum specifications of the CSA 0437.0 Canadian standard.